2017
DOI: 10.1186/s13643-017-0566-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of contextual factors on healthcare quality improvement initiatives: what works, for whom and in what setting? Protocol for a realist review

Abstract: BackgroundContext shapes the effectiveness of knowledge implementation and influences health improvement. Successful healthcare quality improvement (QI) initiatives frequently fail to transfer to different settings, with local contextual factors often cited as the cause. Understanding and overcoming contextual barriers is therefore crucial to implementing effective improvement; yet context is still poorly understood. There is a paucity of information on the mechanisms underlying how and why QI projects succeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 47 publications
1
74
0
Order By: Relevance
“…The review was conducted and reported in accordance with the Realist And Meta-narrative Evidence Syntheses: Evolving Standards (RAMESES) guidance and publication standards [31,32]. No changes were made to the published review protocol [33].…”
Section: Methodsmentioning
confidence: 99%
“…The review was conducted and reported in accordance with the Realist And Meta-narrative Evidence Syntheses: Evolving Standards (RAMESES) guidance and publication standards [31,32]. No changes were made to the published review protocol [33].…”
Section: Methodsmentioning
confidence: 99%
“…Management, culture and systems for better quality and safety have been the main topics in Norwegian national healthcare policy [1][2][3]. These key challenges have also been highlighted internationally [4][5][6][7]. There is a clear need to ensure leadership, a culture of openness and learning, and a system for developing, embedding and sustaining quality and safety improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Yet studying context is challenging9 12 13 The definition of context in QI has evolved in recent years, but remains broad: ‘the physical and sociocultural make-up of the local environment (eg, external environmental factors, organisational dynamics, collaboration, resources, leadership and the like), and the interpretation of these factors (“sense-making”) by the healthcare delivery professionals, patients and caregivers that can affect the effectiveness and generalisability of intervention(s)’ 14. Context is a ‘slippery thing’15 that can be difficult to apprehend due to its dynamism, multiple interacting levels and blurred boundaries 12…”
mentioning
confidence: 99%